EDUCATION – UPBRINGING THOUGHTS OF SOPBOSLI SIPIRA JIROV (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The article talks about the significance of the educational views of Supbosli Sipira Jirov, the great classical poet of the written literature of the Altin Urda period, the founder of the Karakalpak Jirov school, in the education of young people today.